The Effectiveness of Using the Blooket Gaming Platform in Learning Competitions on Students’ Motivation in Islamic Religious Education - Nur Labibah Syaharani; Ade Abdul Muqit (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
Learning motivation is an important factor in the success of the learning process, particularly in Islamic Religious Education (IRE), as students’ motivation is often low due to monotonous teaching methods and the limited use of interactive learning media. This condition can negatively affect students’ engagement in the learning process and their learning outcomes. This study aims to determine the effectiveness of the Blooket platform as a game-based learning medium in increasing students’ learning motivation in Islamic Religious Education learning at SMK Keluarga Widuri Jakarta. This study employed a quantitative approach using a One Group Pretest–Posttest Design. The subjects were 20 tenth-grade Culinary students at SMK Keluarga Widuri Jakarta selected through purposive sampling. Data were collected through questionnaires and observations. The research instrument was tested using validity and reliability tests, while data analysis was conducted using normality tests and a Paired Sample t-Test with the assistance of SPSS. The results showed a significance value of 0.000 (<0.05), indicating a significant difference in students’ learning motivation before and after the implementation of Blooket. These findings indicate that the Blooket platform was effective in increasing students’ learning motivation and creating a more interactive and engaging learning atmosphere.